Clearing of circulating tumour DNA predicts clinical response to first line tyrosine kinase inhibitors in advanced epidermal growth factor receptor mutated non-small cell lung cancer. (March 2020) - Ebert, Eva Boysen Fynboe; McCulloch, Tine; Hansen, Karin Holmskov; Linnet, Hanne; Sorensen, Boe; Meldgaard, Peter
Graphical abstract: Highlights: EGFR mutations are present in baseline ctDNA in 69 % with advanced disease. Mutations are cleared in 79 % after first line TKI treatment is initiated. Clearing of mutations is a significant positive predictor of treatment outcome. Clearing is additionally predictive of overall survival. The pace of clearing does not affect the treatment outcome. Abstract: Objectives: Epidermal growth factor receptor (EGFR) mutations confer sensitivity to tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer (NSCLC). However, a subset of patients has limited or no response. We investigated the initial dynamics of EGFR mutations detected in circulating tumour DNA (ctDNA) during treatment as a predictive marker of outcome. Methods: A total of 225 patients with advanced EGFR mutated NSCLC were included for consecutive blood sampling in this prospective multicentre study. Out of these, 146 patients received first line TKI and had a baseline blood sample available for EGFR mutation testing with the Cobas® EGFR mutation test V2. For examinations on clearing and clinical outcome, 98 patients who had detectable ctDNA at baseline and at least one follow-up blood sample were included. Results: For patients with EGFR mutations present in plasma at baseline, clearing of mutations from the blood during first line TKI served as a positive predictor for objective response rate (p = 0.0008), progression-free survival (PFS) (p < 0.0001) and overall survival (OS) (p < 0.0001). This was seen both for patients who cleared the ctDNA within the first 7 weeks of treatment and patients who cleared the ctDNA at a slower pace. Baseline mutation presence was a negative predictor for PFS (p = 0.0069) and OS (p = 0.0340). Conclusion: The current study is the first to confirm, in a sizeable Caucasian cohort, that clearing of EGFR mutations predict outcome to first line TKI in patients with EGFR mutated NSCLC.